Effects of preplant soil fumigation on nematode population densities, and on growth and yield of raspberry - Bélair, G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
The effect of preplant soil fumigation on population densities of Pratylenchus penetrans, Xiphinema rivesi, and Meloidogyne hapla and growth of red raspberry (Rubus idaeus) was investigated over a 4-year period. P. penetrans was the most abundant and probably accounted for most of the growth reduction. Soil fumigation increased raspberry fields by 98%, 59%, and 18% in the first, second, and third year of production, respectively. The incidence of crown gall (Agrobacterium tumefaciens) was not correlated with soil populations of P. penetrans or M. hapla.